Analysis of hosting capacity in smart distribution network with solar PV and EV penetrations - Wisuwat Klabwisas; Weerakorn Ongsakul; Singh, Jai Govind; Loc Thai Nguyen; PEA-AIT Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
This thesis focuses on the quantification of solar roof-top photovoltaic (PV) and electric vehicle (EV) in a distribution system of Provincial Electricity Authority (PEA) within the system constrains. The term hosting capacity is used for define the maximum numbers of PV and EV penetration while maintain the system constrains stay in the limitation. All the input parameters and network configuration are derived from PEA data also the PV generation profile from PVWatt website. The different alternatives for maximize numbers of EV penetration when integrating with PV generation is studied and also the effectiveness comparison of those alternatives is included. Results show that PV with 5 kW/house can install every house without violate the system constraints and the numbers of EV penetration is increasing along the PV increased deployment. The effectiveness among alternatives shows in ascending order as follow: PV power factor setting to lagging side, transformer{u2019}s tap changing to maximum position and combined PV p.f. setting and transformers tap changing with hourly scheduling.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Photovoltaic power systems; Electric power distribution; Solar Rooftop